Metal Azolate Frameworks: From Crystal Engineering to Functional Materials - Zhang, Jie-Peng; Zhang, Yue-Biao; Lin, Jian-Bin; Chen, Xiao-Ming (Chemical reviews, 2012)
Zhang et al examine metal azolate frameworks with regard to molecular design and crystal engineering.